Use Of E-Learning In Training Human Resource - Cuong, Nguyen Dang Viet (2010)
This paper reviews the uses of e-learning as a medium in training human resources and examines the perception level of learners towards e-learning content. The finding in this study has attempted to provide some insights about the learners\' perception of e-learning especially focusing on the effectiveness of e-learning. It may be useful as a pedagogical tool for instructors planning learning ventures, and it is beneficial to organizations that may consider e-learning as the learning and training tool.